Serum neurotransmitter analysis of motor and non-motor symptoms in Parkinson’s patients - Fan, Yichun; Yang, Wenping; Wu, Weilan; Wang, Xinjing; Lin, Yuxin; Wu, Linlin; Wang, Jun; Huan, Fei; Ding, Haixia; Gao, Rong (Frontiers in Aging Neuroscience, 2024)
Clinical symptoms of Parkinson’s disease (PD) are classified into motor and non-motor symptoms. Mental disorders, especially depression, are one of the major non-motor manifestations of PD. However, the underlying mechanisms remain poorly understood. In the present study, 21 neurotransmitters associated with mental disorders were measured in serum samples from patients and controls using the ultra-high performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) assay. Additionally, five clinical scales—the MDS Unified Parkinson’s Disease Rating Scale (UPDRS), the Non-Motor Symptoms Scale (NMSS), the Mini-Mental State Examination (MMSE), the Hamilton Anxiety Scale (HAMA), and the Hamilton Depression Scale (HAMD)—were used to evaluate the severity of both motor and non-motor symptoms in PD patients. Analysis of neurotransmitter metabolism revealed significant changes in the tryptophan (Trp) metabolic pathway in PD patients. Specifically, levels of Trp, kynurenine (KYN), kynurenic acid (KA), nicotinamide (NAM), and 5-methoxyltryptamine (MeOTA) were substantially decreased. Additionally, three other excitation/inhibiting amino acids—glutamic acid (Glu), 4-aminobutyric acid (GABA), and aspartic acid (Asp)—also declined. Moreover, neurotransmitter conversion ratios, such as KA/KYN, nicotinamide/niacin (NAM/NA), 5-hydroxytryptophan/tryptophan (5-HTP/Trp), and quinolinic acid/kynurenic acid (QA/KA), provided more dynamic insights into disrupted neurotransmitter metabolism. Correlation analyses between scale scores and neurotransmitter levels showed that concentrations of xanthurenic acid (XA) and the turnover rate of 3-hydroxykynurenine (3-HK) were negatively correlated with UPDRS scores, while 5-hydroxytryptamine (5-HT) and GABA levels were negatively correlated with non-motor symptoms in PD patients. In summary, this study elucidates, for the first time, the potential association and dynamics between altered neurotransmitter metabolism and the etiology of PD in terms of motor and non-motor functions. These findings offer novel biomarkers and therapeutic targets for the treatment of PD.